PENERAPAN MANAJEMEN KONSTRUKSI TERHADAP TIME SCHEDULE PADA PROYEK PENATAAN LAPANGAN GGM - Lepsi Narulita; Asep Dian Heryadiana, ST., S.Pd, MT. (Universitas Majalengka, 2021)
In the implementation of project work, there is often a delay in its implementation, it is caused by several inhibiting factors, including weather factors, procurement of materials and equipment, and no less important is the factor of human resources that are not optimal. Therefore it is necessary to have a good construction management application to find out the extent to which the project implementation process is according to what has been scheduled or vice versa. This research was conducted starting with a field survey, interviews, analysis of the RAB. From the results of the study using the Time Schedule, the plan and the realization of the implementation of work in the field, there are differences with the existence of deviation of work, but the problem of delays in work can be resolved through a project coordination meeting.